Momentum Practicum Using Video Analysis for Graph Interpretation Capabilities - Thoha Firdaus; Arini Rosa Sinensis (Pascasarjana Universitas Pendidikan Indonesia, 2018)
Current technological developments have been widely used in physics research, such as the use of tracker programs used to analyze videos. This is very useful when studying or analyzing motion. This study aims to design physics practicums (momentum and collisions) by analyzing position, speed, and time using video analysis Tracker to improve students' ability in interpreting graphics. The method used in this research is the experimental method. The technique of collecting data uses tracking video using video analysis. The results of this study indicate that the momentum practicum design developed can be used to improve students' ability to interpret graphs. Other physical phenomena can also be analyzed using video analysis Tracker.